Contrasting effects of plant inter‐ and intraspecific variation on community‐level trait measures along an environmental gradient. (3rd June 2013) - Kichenin, Emilie; Wardle, David A.; Peltzer, Duane A.; Morse, Chris W.; Freschet, Grégoire T.; Kitajima, Kaoru
Summary Despite widespread focus on interspecific variation in trait‐based ecology, there is growing evidence that intraspecific trait variability can play a fundamental role in plant community responses to environmental change and community assembly. Here, we quantify the strength and direction of inter‐ and intraspecific plant community trait responses along a 900 m elevation gradient spanning alpine and subalpine plant communities in southern New Zealand. We measured five commonly used leaf traits (i.e. dry matter content, N and P concentrations, leaf area and specific leaf area) on all 31 dominant and subordinate species recorded along the gradient, and examined their species‐specific and community‐level responses to elevation using both abundance‐weighted and nonweighted averages of trait values. By decomposing the variance of community‐level measures of these traits across the gradient, we showed that the contribution of interspecific variation to the response of plant assemblages to elevation was stronger than that of intraspecific variation, for all traits except specific leaf area. Further, the relative contributions of interspecific effects were greater when abundance‐weighted rather than nonweighted measures were used. We also observed contrasting intraspecific trait responses to the gradient among species (particularly for leaf N and P concentrations), and found both positive and negative covariation between inter‐ and intraspecific effects on community‐level trait values. The weak community‐average trait responses to elevation, as found for specific leaf area (SLA) and leaf N and P concentrations, resulted from strong but opposing responses among vs. within species, which are not typically accounted for in species‐based measures of plant community responses. For instance, increasing elevation (and associated factors such as a decrease in soil nutrient availability) favoured the dominance of species with relatively high leaf nutrient concentrations while simultaneously triggering an intraspecific decrease in the leaf nutrient concentrations of these species. The context dependency of positive and negative covariation between inter‐ and intraspecific trait variability, and the species‐specific nature of intraspecific shifts in functional trait values, reveal highly complex plastic responses of plants to environmental changes, and highlights the need for greater consideration of the role that intraspecific variation plays in community‐level processes.